What roles do tonic inhibition and disinhibition play in the control of motor programs? - Benjamin, Paul R.; Staras, Kevin; Kemenes, György (Frontiers in Behavioral Neuroscience, 2010)
Animals show periods of quiescence interspersed with periods of motor activity. In a number of invertebrate and vertebrate systems, quiescence is achieved by active suppression of motor behavior is due to tonic inhibition induced by sensory input or changes in internal state. Removal of this inhibition (disinhibition) has the converse effect tending to increase the level of motor activity. We show that tonic inhibition and disinhibition can have a variety of roles. It can simply switch off specific unwanted motor behaviors, or modulate the occurrence of a motor response, a type of ‘threshold’ controlling function, or be involved in the selection of a particular motor program by inhibiting ‘competing’ motor mechanisms that would otherwise interfere with the carrying out of a desired movement. A suggested general function for tonic inhibition is to prevent unnecessary non-goal directed motor activity that would be energetically expensive. The reason why basic motor programs might be a particular target for tonic inhibition is that many of them involve central pattern generator circuits that are often spontaneously active and need to be actively suppressed for energy saving. Based on this hypothesis, tonic inhibition represents the default state for energy saving and motor programs are switched-on when required by removal of this inhibition.